Teaching Surgery to Medical Students - Sweeney, W. Brian (Clinics in Colon and Rectal Surgery, 2012)
Teaching the discipline of surgery to medical students depends on the practicing clinical surgeon assuming the role of educator. The amount of surgical knowledge to impart and technical skill to train are ever increasing as the duration of time students spend on surgical rotations is decreasing. The intent of this article is to assist those surgeons with minimal formal training in educational methods to enhance their teaching skills. Traditional large-group lecture, small-group sessions, and mentoring are reviewed with special emphasis on medical simulation.
Keywords: medical student education; surgeon educators; medical simulation